التوافق النفسي لدى الاخصائيين - بكاري, هدى; بان, نسرين (University of Eloued جامعة الوادي, 2023)
الملخص: هدفت الدراسة الحالية على التعرف على مستوى التوافق النفسي لدى الأخصائي النفسي، ومعرفة ما إذا أن هناك فروق في مستوى التوافق النفسي على مقياس التوافق النفسي وفقا لمتغير الجنس، والعمر، بالإضافة إلى الخبرة المهنية. ومن أجل معرفة كل هذا وتحقيق أهداف الدراسة اعتمدنا على مقياس التوافق النفسي للدكتورة زينب شقير(2003)، الذي تكون من ( 80 بند)، وتوزعت هذه البنود على أربعة أبعاد وهي (التوافق الشخصي الانفعالي، والثاني التوافق الصحي، وأيضا التوافق الأسري، ثم التوافق الاجتماعي).كل بعد يتكون من 20 بند، حيث تمثلت عينة بحثنا على 30 أخصائيا نفسيا، وإتباع المنهج الوصفي التحليلي، واستخدام الأساليب الإحصائية المتمثلة في المتوسط الحسابي، الانحراف المعياري، اختبار"ت" لدلالة الفروق بين المتوسطات. حيث وصلت نتائج بحثنا على ما يلي أن: ▪ بين النتائج الدالة إحصائيا أن مستوى التوافق النفسي لدى الأخصائي النفسي ذات درجة مرتفعة. ▪ لا توجد فروق دالة إحصائيا بين الذكور والإناث من الأخصائيين النفسانيين على مقياس التوافق النفسي تبين مستوى التوافق بينهم. ▪ وأيضا أظهرت النتائج أنه لا توجد فروق دالة إحصائيا على مستوى العمر ( أقل من 35 سنة / 35 سنة فأكثر) من الأخصائيين النفسانيين على مقياس التوافق النفسي تثبت أن العمر يؤثر في مستوى التوافق النفسي. ▪ لكن النتائج أثبتت أنه توجد فروق دالة إحصائيا أن متغير الخبرة (أقل من 10 سنوات/ 10 سنوات فأكثر) يحدث تغيير ويؤثر على مستوى التوافق النفسي لدى الأخصائيين النفسانيين على مقياس التوافق النفسي. ومن هنا يمكننا أن نقول أن أغلبية الأخصائيين النفسانيين ذا مستوى مرتفع من التوافق النفسي. وأيضا أن عامل الجنس والعمر لا يؤثر في مستوى التوافق النفسي للأخصائيين النفسانيين، وأن عامل الخبرة ومدى تعامل الأخصائيين مع المرضى والتجارب المهنية الطويلة وتمكنه من العمل الذي يقوم به يؤثر في درجة التوافق النفسي لديهم.وهذا يبقى حيز تحت إطار العينة المدروسة. Résumé : فرنسية أو انجلزية The current study aimed to identify the level of psychological adjustment of the psychologist, and to find out whether there are differences in the level of psychological adjustment on the scale of psychological adjustment according to the variables of gender, age, in addition to professional experience. In order to know all this and achieve the objectives of the study, we relied on the psychological compatibility scale of Dr. Zainab Choucair (2003), which consisted of (80 items). Social). Each dimension consists of 20 items, as our research sample consisted of 30 psychologists, following the analytical descriptive approach, and using statistical methods represented in the arithmetic mean, standard deviation, and the "T" test to indicate differences between the means. Where the results of our research reached the following: ▪ The statistically significant results show that the level of psychological adjustment of the psychologist is high. ▪ There are no statistically significant differences between male and female psychologists on the scale of psychological adjustment showing the level of agreement between them. ▪ Also, the results showed that there are no statistically significant differences at the level of age (less than 35 years / 35 years and over) of psychologists on the psychological adjustment scale proving that age affects the level of psychological adjustment. ▪ However, the results proved that there are statistically significant differences that the experience variable (less than 10 years / 10 years and more) changes and affects the level of psychological adjustment among psychologists on the scale of psychological adjustment. Hence, we can say that the majority of psychologists have a high level of psychological compatibility. Also, the factor of gender and age does not affect the level of psychological compatibility of psychologists, and that the factor of experience and the extent of the specialists' dealing with patients and long professional experiences and their ability to do the work that they do affect the degree of psychological compatibility with them. This remains a space under the framework of the studied sample. الكلمات المفتاحية: عربيّــة: التوافق. اخصائي . الخبرة فرنسيــة او إنجليزية: Haiku Hair, Greens Twin, Nature, Condensation.
تخصص علم نفس